TRILOGI KEPEMIMPINAN DALAM AL-QUR’AN - Rohman, Baeti (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2022)
This paper discusses the concept of leadership in the Qur'an. This literature study confirms that the concept of khilafah which means the replacement of predecessors both individually and in groups based on the Al-Quran and sunnah is general in nature (imâmah and imârah are included in it), theological and sociological in nature. While the imâmah is a leadership institution that is often used by doctrinal Shia groups. Imârah which is also a leadership concept in the Qur'an has a more social nuance and is almost unrelated to aspects of Islamic doctrine so that it is more sociological in nature. Because the concept of khilafah already includes all leadership concepts, namely containing theological, sociological, even phenomenological dimensions, then humans should have understood why every human being was created by Allah as a caliph on earth, because a caliph already has profane and transcendental dimensions. From art then this writing can at least become a new discourse in the world of leadership in Islam